Community and Parents Perception towards Teenage Pregnancy and Teenage Motherhood at Korle – Gonno - Aidoo, B.J. (University of Ghana, 2017)
Teenage pregnancy is the situation in which a girl gets pregnant between the ages of 13 to 19 years. Teenage pregnancy and teen motherhood are global matters of public health concern. The aim of the study was to investigate the perceptions of teenagers and parents toward teenage pregnancy and teenage motherhood in Korle-Gonno, in the Greater Accra Region. The study generally explored the community knowledge and attitude towards teenage pregnancy and teenage motherhood, examined the socio- cultural factors that influence teenage pregnancy and finally assessed the social and economic aspects of teenage pregnancy among teenagers and parents. The study adopted a qualitative method using focus group discussion (FGD) and in-depth interview techniques to gather data. A sample of 40 participants was involved in the study. Out of this number, four (4) FDGs were done, comprising one (1) male group of artisans, one (1) male group organized from the community, one (1) female group and the final group made of students of adolescent age. In addition, a total of eight (8) in-depth interviews (IDI) were also conducted. Transcription was done verbatim after interviewing participants and the data analysed by qualitative methods to draw conclusions. It was observed that the most common reasons for girls to engage in sex at a young age are poverty, the desire for material goods, family and peer pressure and to a much lesser extent pleasure. This study also found the teenagers involved in sexual activities are misinformed or do not like the idea of using contraceptives. The study also revealed that lack of proper parental control was also a major factor contributing to teenage pregnancy in the community. Lack of reproductive health education was also a major contributing factor. The study concludes that unstable marriages, unemployment, lack of sexual reproductive health education, low –income and peer pressure are major factors that cause the high rate of teenage pregnancy in the Korle-Gonno Community. Although the youth have negative attitude towards teenage pregnancy, their perception and understanding of sexuality and contraception is very poor. There is therefore the need for serious teen pregnancy prevention intervention programmes to address specific needs and priorities of the Korle- Gonno Community
Keywords: Teenage pregnancy; community; public health